FORMATION OF EATING BEHAVIOR IN CHILDREN - Kasymova Iroda Khusan kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This article presents a literature review from the past five years along with the author’s reflections on the formation of eating behavior in children. It also includes data from a 2023 study published in the Academic Research in Educational Sciences review, as well as findings from ASPEN (American Society for Parenteral and Enteral Nutrition) 2025, which analyzed the eating behavior of school-aged children depending on the type of feeding and caregiving principles.